Improving the Usability of the Sumber Alam Express Ticket Booking Application using the Heuristic Evaluation Method - Kurniawan, Rizki Candra; Frobenius, Arvin Claudy (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
This study aims to evaluate improvements in the usability quality of the Sumber Alam Express application prototype using the Heuristic Evaluation method. The test results show that out of the ten heuristic evaluation factors, nine received high/agree ratings, while one factor received a moderate/neutral rating. There was a significant improvement across all factors compared to the previous study. Notably,